Ultrafast carrier dynamics of metal halide perovskite nanocrystals and perovskite-composites. Issue 20 (9th May 2019) - Mondal, Navendu; De, Apurba; Das, Somnath; Paul, Sumanta; Samanta, Anunay
Abstract : Studies on ultrafast dynamics of various photo-induced processes in perovskite nanocrystals and their composites, and insights obtained from them are presented in this review. Abstract : Perovskite nanocrystals (NCs), especially those based on cesium lead halides, have emerged in recent years as highly promising materials for efficient solar cells and photonic applications. The key to realization of full potential of these materials lies however in the molecular level understanding of the processes triggered by light. Herein we highlight the knowledge gained from photophysical investigations on these NCs of various sizes and compositions employing primarily the femtosecond pump–probe technique. We show how spectral and temporal characterization of the photo-induced transients provide insight into the mechanism and dynamics of relaxation of hot and thermalized charge carriers through their recombination and trapping. We discuss how the multiple excitons including the charged ones (trions), generated using high pump fluence or photon energy, recombine through the Auger-assisted process. We discussed the harvesting of hot carriers prior to their cooling and band-edge carriers from these perovskite NCs to wide band-gap metal oxides, metal chalcogenide NCs and molecular acceptors. How perovskites can influence the charge carrier dynamics in composites of organic and inorganic semiconductors is also discussed.